Implementation of the JKN-Mobile Application at the Mangkubumi Health Center Tasikmalaya City in 2024 - Putri, Aisah Nindiani Putri; Sukawan, Ari (BPJS Kesehatan, 2025)
The implementation of technology and information is currently starting to be applied in the health sector. The JKN Mobile Application is an effort to improve services for BPJS Health participants. The largest number of JKN Mobile users in Tasikmalaya City is at the Mangkubumi Health Center, which has 3,528 users. However, there are problems, namely a lack of communication with patients, no resources in the form of pamphlets or banners, patients having never used the doctor consultation feature, and no Standard Operating Procedure (SOP) for doctor consultations being available. This research aims to determine the supporting and inhibiting factors influencing the JKN Mobile Implementation process. The benefits of this study are that it provides insight and public interest in the features of the JKN Mobile and a means of implementing the electronic medical record, a type of qualitative research with a phenomenological approach. The sampling technique is purposive sampling with a total of 5 (five) subjects. The data collection techniques were interviews, observation, and documentation. Implementing JKN Mobile has supporting factors, including Two-way communication, JKN Mobile information posters, adequate technological facilities and infrastructure, an integrated information system, good response from staff and patients, and online registration SOPs. Meanwhile, inhibiting factors include system and user constraints, the lack of human resources managing JKN Mobile, and the absence of an online registration flow banner.